Climate change-related growth improvements in a wide niche-breadth tree species across contrasting environments - Fajardo, Alex; Gazol, Antonio; Meynard, Paulo Moreno; Mayr, Christoph; Pastur, Guillermo J. Martinez; Peri, Pablo L.; Camarero, J. Julio (Annals of Botany, 2023)
Background and Aims The vulnerability and responsiveness of forests to drought are immensely variable across biomes. Intraspecific tree responses to drought in species with wide niche breadths that grow across contrasting climatically environments might provide key information regarding forest resistance and changes in species distribution under climate change. Using a species with an exceptionally wide niche breath, we tested the hypothesis that tree populations thriving in dry environments are more resistant to drought than those growing in moist locations. Methods We determined temporal trends in tree radial growth of 12 tree populations of Nothofagus antarctica (Nothofagaceae) located across a sharp precipitation gradient (annual precipitation of 500-2000 mm) in Chile and Argentina. Using dendrochronological methods, we fitted generalized additive mixed-effect models to predict the annual basal area increment as a function of year and dryness (De Martonne aridity index). We also measured carbon and oxygen isotope signals (and estimated intrinsic water-use efficiency) to provide potential physiological causes for tree growth responses to drought. Key Results We found unexpected improvements in growth during 1980-1998 in moist sites, while growth responses in dry sites were mixed. All populations, independent of site moisture, showed an increase in their intrinsic water-use efficiency in recent decades, a tendency that seemed to be explained by an increase in the photosynthetic rate instead of drought-induced stomatal closure, given that delta O-18 did not change with time. Conclusions The absence of drought-induced negative effects on tree growth in a tree species with a wide niche breadth is promising because it might relate to the causal mechanisms tree species possess to face ongoing drought events. We suggest that the drought resistance of N. antarctica might be attributable to its low stature and relatively low growth rate.
CRIS-Team WoS Importer:2023-05-26